Embedding social accountability in the medical school and its curricula: Patan Academy of Health Sciences, Nepal - Shrestha, Shrijana; Gongal, Rajesh Nath; Baral, Kedar Prasad; Acharya, Paras Kumar; Yadav, Bharat Kumar; Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Patan Academy of Health Sciences (PAHS) was established in 2008 with a social accountability mandate and the mission to produce competent and committed health professionals to serve the rural and underserved population. Enrolment of undergraduate medical students started from 2010. This article describes the context and process for the establishment of the Academy, the approaches taken and some of the early outputs. Method: The information was collected from the policy documents, PAHS website, meeting minutes/ discussions, feedbacks and medial school records. All the information were compiled and presented under different headings/subheadings in a phase wise manner. Result: PAHS has been actively engaged in a multitude of partnerships from local to global and has chosen the best and most applicable innovations from around the world. The integrated suite of innovations the Academy has developed includes its admission policy, teaching-learning methodologies, community-based learning, scholarship-schemes and service bonds. The PAHS School of Medicine has successfully enrolled undergraduate medical students from all over the country, representing ethnic diversity, remote/rural background, underprivileged communities and gender balance. More than 50% graduates from the first five-batches are successfully deployed into primary level peripheral health facilities of the government health system. Conclusion: The initial reports and observations confirm that the integrated measures taken by the Academy have been effective in enrolling the right students, educating them in an effective way and deploying them to address the country’s need. A longer follow-up on rural retention and performance evaluation is needed to conclusively establish the outcome of the school.